HUBUNGAN RESILIENSI MATEMATIS TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MAHASISWA PADA MATA KULIAH MATEMATIKA DASAR - Ade Evi Fatimah; Azrina Purba; Yulia Anita Siregar (Mahesa Research Center, 2020)
This study aims to determine the relationship and the extent of influence between mathematical resilience and students' mathematical problem-solving abilities in basic mathematics courses. This research is motivated by the perception of students who tend to be negative towards mathematics as well as an attitude of lack of confidence and easily give up in solving the given questions. In addition, students' mathematical solving abilities are also classified as low, even though this ability is very important because it is the basis and general goal of learning mathematics. The method used in this research is quantitative descriptive method. The population in this study were all Semester I students of the Computer and Informatics Engineering study program at STKIP AL Maksum Langkat which consisted of 5 classes and took basic mathematics courses, while the research sample was taken using purposive sampling technique, which is a technique of determining and taking the specified sample. by researchers with certain considerations. The sample consisted of 35 students. The instruments in this study were test questions in the form of mathematical problem-solving abilities and non-test questions in the form of a mathematical resilience scale. Then the data is processed using hypothesis testing techniques, correlation analysis and simple regression assisted by SPSS and Microsoft Excel. The results showed that there was a positive relationship between mathematical resilience and students 'mathematical problem-solving abilities with the effect of mathematical resilience by 41.3% on students' mathematical problem-solving abilities.